2014
DOI: 10.1371/journal.pone.0096695
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Up-Regulates the Vitamin D Receptor by Protecting It from Proteasomal Degradation in Human CD4+ T Cells

Abstract: The active form of vitamin D3, 1,25(OH)2D3, has significant immunomodulatory properties and is an important determinant in the differentiation of CD4+ effector T cells. The biological actions of 1,25(OH)2D3 are mediated by the vitamin D receptor (VDR) and are believed to correlate with the VDR protein expression level in a given cell. The aim of this study was to determine if and how 1,25(OH)2D3 by itself regulates VDR expression in human CD4+ T cells. We found that activated CD4+ T cells have the capacity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
63
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 72 publications
11
63
3
Order By: Relevance
“…We found that 1,25(OH) 2 D 3 strongly inhibited IFNγ production (~15-fold) at physiological concentrations (60–110 pM) (Figure 1A). Furthermore, we found that 25(OH)D 3 at physiological concentrations (50–125 nM) inhibited IFNγ production to the same degree as 1,25(OH) 2 D 3 (Figure 1A), which confirms that T cells have the ability to convert the inactive 25(OH)D 3 to the active 1,25(OH) 2 D 3 (46, 47). It is well known that anti-CD3/CD28 bead stimulation promotes expansion of CD4 + T cells (48).…”
Section: Resultssupporting
confidence: 62%
“…We found that 1,25(OH) 2 D 3 strongly inhibited IFNγ production (~15-fold) at physiological concentrations (60–110 pM) (Figure 1A). Furthermore, we found that 25(OH)D 3 at physiological concentrations (50–125 nM) inhibited IFNγ production to the same degree as 1,25(OH) 2 D 3 (Figure 1A), which confirms that T cells have the ability to convert the inactive 25(OH)D 3 to the active 1,25(OH) 2 D 3 (46, 47). It is well known that anti-CD3/CD28 bead stimulation promotes expansion of CD4 + T cells (48).…”
Section: Resultssupporting
confidence: 62%
“…There have been conflicting results regarding the expression of VDR in non‐stimulated CD4 + T cells. Some studies have reported VDR expression in non‐stimulated T cells , whereas other studies have reported no VDR expression . Our results support the low expression of VDR in unstimulated CD4 + T cells.…”
Section: Discussionsupporting
confidence: 88%
“…Calcitriol targets also included genes involved in a variety of metabolic, detoxification, nuclear receptor‐related, and other pathways (Table S3). Supporting post‐translational regulation by vitamin D, as described in several systems , VDR was not identified as a significant regulated gene in the RNA‐seq analysis.…”
Section: Resultsmentioning
confidence: 78%